SALMONELLA INFECTION IN MICE - ZOZAYA, JOSE; VARELA, GERARDO (My University, 1941)
Of 306 white mice which died spontaneously, 76 contained Salmonella spp The numbers of mice killed by different spp were: S typhimurium, 59; S paratyphi A, 16; S choleraesuis, 1 The vars of S t-m identified were: S t-m var Binns, 18; var C
CIENC MEX
Keywords: SALMONELLA, INFECTION, MICE; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL